2023
DOI: 10.1111/vco.12888
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of canine oral extramedullary plasmacytoma over a 15‐year period (July 2004–July 2019): Treatment, histologic parameters and clinical outcomes

Abstract: A total of 45 cases of canine oral extramedullary plasmacytomas (EMPs) presented to a tertiary referral institution over a 15‐year period were examined. Histologic sections of 33 of these cases were examined for histopathologic prognostic indicators. Patients underwent variable treatment including surgical intervention, chemotherapy and/or radiation therapy. Long term survival was observed in the majority of dogs with a median survival time of 973 days (2–4315 days). However, almost 1/3 of dogs had progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Indeed, in humans, although EMPs generally have a good prognosis, 11–36% of cases have been reported to proceed to MM [ 40 , 41 , 42 ]. Some studies in canines have found EMPs tend to be benign (although oral EMPs are locally aggressive), carrying an excellent prognosis following complete surgical excision [ 1 , 2 , 43 , 44 ], although a recent study found that up to a third of cases had a progression of plasma cell disease, with two cases showing myeloma-like progression [ 45 ], and there are occasional case reports of dogs with EMPs showing progression to a disseminated myeloma [ 46 ]. However, cutaneous involvement in patients with MM is very uncommon and usually occurs in the late stages of the disease, with the development of multiple skin lesions reflecting the increased tumour cell burden [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in humans, although EMPs generally have a good prognosis, 11–36% of cases have been reported to proceed to MM [ 40 , 41 , 42 ]. Some studies in canines have found EMPs tend to be benign (although oral EMPs are locally aggressive), carrying an excellent prognosis following complete surgical excision [ 1 , 2 , 43 , 44 ], although a recent study found that up to a third of cases had a progression of plasma cell disease, with two cases showing myeloma-like progression [ 45 ], and there are occasional case reports of dogs with EMPs showing progression to a disseminated myeloma [ 46 ]. However, cutaneous involvement in patients with MM is very uncommon and usually occurs in the late stages of the disease, with the development of multiple skin lesions reflecting the increased tumour cell burden [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…EMP progresses to multiple myeloma in approximately 30% of patients in human medicine 4,5 . However, the patient shows no corresponding symptoms regarding multiple myeloma, and serum globulin level is normal without monoclonal spike.…”
Section: Discussionmentioning
confidence: 99%